Influence of seed type on forage production of panicum maximum cultivars - de Oliveira, Elisa Pereira [UNESP]; Teodoro, Paulo Eduardo; da Silva Junior, Carlos Antonio; Benites, Simone Botelho; Ribeiro, Larissa Pereira; Torres, Francisco Eduardo (Science Alert, 2016)
Objective: The aim of this study was to evaluate the influence of seed type and sampling times in the agricultural year 2011/2012 on the production of Dry Mass (DM) of cultivars of Panicum maximum. Methodology: The experiment was carried out at the Universidade Estadual de Mato Grosso do Sul, Campus Aquidauana-MS. The statistical design was a randomized block in a split plot with four replications. The plots consisted of three cultivars of Panicum maximum: Tanzânia, Mombaça and Massai. The subplots comprised two seed treatments: Conventional seed with high purity and seed encrusted, who went through the process of chiseling, fungicide and subsequently received péleti containing macro and micronutrients. The first cut occurred on 22 October, 2011 the remaining forage cuts were 60 days of regrowth, which it was assessed the following parameters: Dry mass of leaves, culm and roots and leaf/culm ratio (L/C). Results: The seed coating did not affect the production of DM. Mombaça showed greater DM and leaf/culm ratio in relation to Tanzânia and Massai. Conclusion: In the region of Aquidauana-MS, Panicum maximum cultivars showed low forage production during the winter season, characterizing the summer as the best period of forage production for the three cultivars of this species.
Keywords: Dry mass; Forage production; Grass colonião; Leaf/culm ratio; Seed types